ФОРМУВАННЯ ПРОФЕСІЙНИХ РИС ПЕДАГОГА В УМОВАХ ВИЩОЇ ШКОЛИ (Педагогіка вищої та середньої школи, 2022)
The essence of the professional aspect of a contemporary teacher, his main characteristics, and ways of his making under conditions of higher pedagogical school are disclosed in this article.